KESESUAIAN DAN DAYA DUKUNG EKOWISATA MANGROVE DI DESA KURAU DAN DESA KURAU BARAT KABUPATEN BANGKA TENGAH - Meli Zulia; Okto Supratman; Suci Puspita Sari; Okto Supratman (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
ABSTRACT Mangrove ecosystems are one ecosystem that is vulnerable damaged. Mangrove ecotourism is one of the efforts that can do to reduce damage in the utilization of mangrove ecosystems.This study aims to calculate the suitability and carrying capacity of mangrove ecotourism in the Kurau Village and West Kurau Village, Central Bangka Regency. This research was conducted in March 2019 at the Mangrove ecotourism area of ​​Kurau Village and West Kurau Village. The study location determined using a purposive sampling method consisting of 3 substations in one location to get primary data and secondary data. Descriptive method was used to analyze the Tourism Suitability Index (IKW) and the Regional Carrying Capacity (DDK). The calculation results show that the mangrove ecotourism area of ​​Kurau Village is included in the suitable category (S2) with a Suitability Index value is 74.36% and the Regional Carrying Capacity (DDK) is 44 people per day (10 hours / day) and West Kurau Village is included in suitable category (S2) with a Suitability Index value of 74.36% and the Regional Carrying Capacity (DDK) is 55 people per day (10 hours open / day).